The impact of social support on students' mental health: A new perspective based on fine art majors - Wei, Pengju (Frontiers in Psychology, 2022)
At present, more and more college students are facing a variety of challenges, the degree of psychological health of college students will directly affect whether they can meet the challenges, and a good psychological state can also help college students better career development and improve the degree of social integration. This paper uses the SCL-90 Symptom Self-Assessment Scale and the Social Support Rating Scale (SSRS) to investigate the mental health, psychological support and social support of poor students in two universities in Hainan City. The research results showed that there was no significant difference between the objective support scores of the poor students in higher vocational colleges and the non-poor students, while the subjective support and the utilization of support scores were significantly lower than those of the non-poor students. In essence, a successful social support should not only be a one-dimensional support for the subject to the object, but should be a process of two-sided interaction, or a process of "mutual construction" between supporters and supported. According to the research conclusions, this paper finally put forward how to improve the degree of mental health of college students, especially should form a comprehensive educational environment including campus culture construction, ideological and moral education, and economic help system.